Psychoeducational Media as a Coping Strategy to Alleviate Academic Stress Among High School Students: A Systematic Literature Review - Taufik Hidayat; Agus Efendi; Akhmad Arif Musadad (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Academic stress experienced by high school students can negatively affect mental health, academic achievement, deviant behavior, sleep quality, physical health, school dropout, and long-term outcomes. This study aims to systematically review scholarly literature on the use of psychoeducational media as a coping strategy to reduce academic stress among high school students. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Articles were retrieved from the Scopus database using inclusion criteria, including publications published between 2015 and 2025, within the subject areas of “psychology” and “social sciences,” written in English, open access, focused on academic stress in high school students, and examining psychoeducational media. 5 articles were finally included for thematic analysis. The results indicate that psychoeducational media, including gratitude journals, mindset modules, and multimodal programs (HSMP, MSC-T, and EASE), are effective in reducing academic stress and related psychological distress. These interventions also improve emotional regulation, self-compassion, and psychological well-being. The findings highlight the potential of psychoeducational media to be integrated into school-based mental health promotion. However, further research is needed to examine the long-term effectiveness and cultural relevance of these interventions in various educational settings.